Estimating number of European eel (Anguilla anguilla) individuals using environmental DNA and haplotype count in small rivers - Silje Halvorsen; Lars Korslund; Morten Mattingsdal; Audun Slettan (Ecology and Evolution, 2023)
Abstract Knowledge about population genetic data is important for effective conservation management. Genetic research traditionally requires sampling directly from the organism, for example tissue, which can be challenging, time‐consuming, and harmful to the animal. Environmental DNA (eDNA) approaches offer a way to sample genetic material noninvasively. In attempts to estimate population size of aquatic species using eDNA, researchers have found positive correlations between biomass and eDNA concentrations, but the approach is debated because of variations in the production and degrading of DNA in water. Recently, a more accurate eDNA‐approach has emerged, focusing on the genomic differences between individuals. In this study, we used eDNA from water samples to estimate the number of European eel (Anguilla anguilla) individuals by examining haplotypes in the mitochondrial D‐loop region, both in a closed aquatic environment with 10 eels of known haplotypes and in three rivers. The results revealed that it was possible to find every eel haplotype in the eDNA sample collected from the closed environment. We also found 13 unique haplotypes in the eDNA samples from the three rivers, which probably represent 13 eel individuals. This means that it is possible to obtain genomic information from European eel eDNA in water; however, more research is needed to develop the approach into a possible future tool for population quantification.